Pengaruh Pelatihan dan Pengembangan Sumber Daya Manusia (SDM) terhadap Kinerja Pegawai PT Perkebunan Nusantara II Kebun Patumbak - Firmansyah, Ridho; Yusrita, Yusrita; Nasution, Ismail (JRMB (Jurnal Riset Manajemen & Bisnis), 2024)
The formulation of the problem in this study is whether there is an influence of training and human resource development on employee performance, both partially and simultaneously. The purpose of this study is to determine the influence of training and human resource development on employee performance, both partially and simultaneously. The population of this study was 34 people and the sample in this study was 34 people using saturated sampling. The data source for this study uses primary data, namely sources recorded directly by researchers through questionnaires and interviews regarding problems related to training and human resource development on employee performance. The data analysis technique used is multiple linear regression. The results of the study indicate that training has a positive and significant effect on employee performance, human resource development has a positive and significant effect on employee performance. Training and human resource development has a positive and significant effect on employee performance.